Quantum Chemical Studies on NiO Nanoclusters (Journal of Atomic and Molecular Sciences, 2013)
The structural stability of nickel oxide (NiO)$_n$ $(n=1$~$7)$ nanoclusters werestudied using Gaussian 03W program package with B3LYP/6-31G level basis set. It isobserved that the ring structure is more stable in most cases compared to other structures(Linear and 3D). For $n > 6$ the 3D structure is no longer stable. From the optimizationresults of (NiO)$_n$ clusters it is found that when the atoms in the cluster increasesit leads to the increase in the stability. The dipole moment of each cluster is also studiedwhich shows that the dipole moment depends upon the arrangement of atoms inthe cluster. The HOMO LUMO gap, ionization potential, electron affinity and bindingenergies of Nickel Oxide clusters have been calculated and reported.